Numerical Investigation of Ground Cooling Potential for Malaysian Climate - Mohd Yusof, Taib; Shahrani, Anuar; Hassan, Ibrahim (2013)
Geographically, Malaysia located between 1° and 7° in North latitude and 100° and 120° in East longitude with the average daytime temperature about 31°C. However, temperature at 24°C is commonly applied for human comfort in commercial and residential building which is increasing the demand of electricity for cooling. This leads to the utilization of renewable energy and source of thermal storage such as ground [Shekerchian et al., 2012]. Ground has high thermal inertia in which about 46% energy from the sun is absorbed by the earth which makes temperature fluctuations at the ground surface attenuated deeper in the ground. At a sufficient depth, the ground temperature is lower than the outside temperature. When ambient air is drawn through buried pipe called ground heat exchanger (GHE), the air is cooled [Pfafferott, 2003]. This air can be used for human comfort by means of ventilation and can be used for other application. Towards of GHE implementation, this paper discusses underground temperature variation with considering different depth and thermal diffusivity based on mathematical model.